The Effect Of Training And Work Motivation On The Performance Of Village Office Employees In Seginim District, South Bengkulu Regency - Mardhiyah Dwi Ilhami; Taufik Bustam; Gegen Prasetyo (Journal of Indonesian Management, 2023)
This study aims to determine "The Effect of Training and Work Motivation on the Performance of Village Office Employees in Seginim District, South Bengkulu Regency", both partially and simultaneously. The type of research used is quantitative research. The population in this study was 127 village office employees in Seginim District, South Bengkulu Regency, using the total side technique, which means that all populations were used as research samples.Based on the t test, it is known that the calculated t value in the training variable of 4.843 is greater than the table t which is 1.960 with the probabilility t which is a sig value of 0.000 which is smaller than the significance limitation of 0.05. Based on the test results, the training variables have a positive and significant effect on employee performance. In the work motivation variable, the calculated value of 4.536 is greater than t table, which is 1,960 with a probabilility t, which is a sig value of 0.000 which is smaller than the significance limitation of 0.05. Based on the results of these tests, the variable work motivation has a positive and significant effect on employee performance. Based on the results of the F test, it was found that the calculated F value was 256,196 greater than F table 2.68 with a sig value of 0.000 smaller than 0.05, which showed that Ho was rejected and Ha was accepted, meaning that training and work motivation together had a positive and simultaneous effect on employee performance variables. The R square value obtained is 0.805. This figure shows that employee performance can be explained by training and work motivation of 80.5%.